Evaluation of an ectomycorrhizal macrofungi as an indicator species of high conservation value pine-heath forests in northern Sweden - Lindman, Jenny (2011)
Since the 1950s, the development of modern rotation forestry in boreal Fennoscandia has resulted in a severe reduction of older forests, and a high degree of fragmentation among the small patches that remains of old forest. In Sweden, when performing conservation value assessments in order to identify and preserve the remaining forest habitats, the government authorities use to a significant extent a set of indicator species that indicate habitats of high biological conservation value. One species considered to indicate high conservation values in pine-heath forests is the red-listed ectomycorrhizal (EM) macrofungi Sarcodon scabrosus (Fr.) P. Karst. In the present study, the validity of using S. scabrosus as an indicator species was evaluated by performing a survey including 41 pine-heath habitats in northern Sweden. In each stand, the occurrence and abundance of S. scabrosus was quantified together with occurrence of other red-listed macrofungi and different structural variables related to stand and tree continuity, historical disturbances, ground vegetation and soil type. Results were analysed by performing single and multiple regressions based on the maximum number of observed S. scabrosus sporocarps, and using 2-sample T-tests comparing stands with and without occurrences of the species. Results revealed that the occurrence of S. scabrosus neither is correlated with the presence of other red-listed macrofungi, nor with none of the studied parameters indicating long stand and tree continuity. In fact, occurrence of the species was negatively correlated to increasing tree age, but positively correlated to variables related to an open stand structure (low basal area, abundance of pine seedlings, a wide tree diameter range) and a proportionally high amount of needle dominated litter on the ground. The negative correspondence with tree age may be related to a reduced production of needle biomass in older trees, which may reduce nutrient availability for S. scabrosus. To analyse the distribution of S. scabrosus ...